Die Konzeptualisierung der Graphomanie in der russischsprachigen postmodernen Literatur - Tchouboukov-Pianca, Florence (Slavistische Beitraege, 1995)
The author examines the tradition of graphomania in Russian literature of the 19th and 20th centuries and asks what it is used for in this literature and in particular for Chlebnikov.